POTRET EKSPLOITASI PEREMPUAN OLEH PENULIS PEREMPUAN DALAM SUSASTRA ANGKATAN 2000-AN: KAJIAN FEMINISME DALAM SUSASTRA INDONESIA - Nanik Setyawati; Zainal Arifin; Larasati .; Icuk Prayogi (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
Research about exploitation of female author toward woman on 2000s period litterature is so important for mapping of litterature history, reading refereces, and refereces for teacher litterature. This reseacrh will reveal how does the form of female author exploitation toward woman, all at once to reveal a track record of the author life. The approach used on this research is receptive approach in litterature. Receptive approach is one of approcah that use teh reader point of view to get some reseach datas. The sources of the research are litterature texts produced by female author on 2000s period and litterature readers that contain woman exploitation by female author on 2000s period. Several litterature that represented delegation of female author has been decided to limit the extent of data source. They are Ayu Utami (Saman), Dewi Lestari (Supernova: Ksatria, Putri, dan Bintang Jatuh), Fira Basuki (Jendela-jendela), dan Djenar Mahesa Ayu (Jangan Main-main (Dengan Kelaminmu)). Based on the result, according to the reader reception, female authors who exploit woman, on average have a way of exposure vulgar story, put?é?á woman life on the hedonic sphere, have a denotative style of language (use a less conotative), so brave to expose female vital organ, and not hesitate to talking about ?óÔé¼?£vagina?óÔé¼Ôäó and breast. Whereas the conclustion from the author?óÔé¼Ôäós life track record, those female authors on average are within biologically productive age. About their education, those authors are educated people and have a job in political sector. However, they often againt such of problem with family, especially the problem of divorce. ?é?á Key words: woman exploitation, female author, 2000s period litterature, feminisme.